Dynamically downscaled future projections of the Northwest Atlantic Ocean across low to high emissions scenarios - Dongmin Kim; Andrew C. Ross; Sang-Ik Shin; Fabian A. Gomez; Jasmin G. John; Denis L. Volkov; Sang-Ki Lee; Michael A. Alexander; Charles A. Stock (Ocean Science, 2026)
We used a high-resolution (1/12°) Modular Ocean Model version 6 implementation for the Northwest Atlantic Ocean (MOM6-NWA12) to dynamically downscale Geophysical Fluid Dynamics Laboratory Earth System Model version 4.1 (GFDL-ESM4.1) projections for the 21st century. Simulations were conducted under four different Coupled Model Intercomparison Project Phase 6 emission scenarios. MOM6-NWA12 accurately simulates the spatial patterns of sea surface temperature, salinity, and dynamic sea surface height (SSH) during the historical period. In particular, the Gulf Stream's strength, position, recirculation, and separation from the US East Coast are significantly improved in MOM6-NWA12 compared to the coarse-resolution GFDL-ESM4.1. Projected end-of-century warming varied strongly between scenarios, from ∼4 °C under prior “worst case” emissions scenarios (SSP-585), 2∼3 °C under intermediate scenarios (SSP-245, SSP-370) more consistent with current trajectories, to ∼1 °C under aggressive mitigation (SSP-126). Consistent with a significant weakening of the Atlantic Meridional Overturning Circulation projected by GFDL-ESM4.1, MOM6-NWA12 shows a substantial volume transport reduction in the Western Boundary Current (WBC) system (i.e., Yucatan Current, Florida Current, Antilles Current, and the Deep Western Boundary Current) toward the late 21st century (between 23 % and 38 %, varying by scenario). This projected weakening of the WBC system and the associated reduction in the coastal upwelling of cold, fresh subsurface waters lead to a significant increase in ocean temperature, salinity, and dynamic SSH along the US southeast and northeast Coasts, particularly in the South Atlantic Bight.